Financial Independence, Operational Challenges, and Best Practices of the Sangguniang Kabataan in a Highly Urbanized City in Western Visayas, Philippines - Reguindin, John Christopher V.; Caelian, Merlita V. (Philippine Social Science Journal, 2025)
Rooted in the Sangguniang Kabataan (SK) Reform Act of 2015, this study evaluates the financial independence of SK officials in a highly urbanized city, Western Visayas, Philippines. Using an explanatory sequential mixed-method design, the research assessed SK autonomy regarding allocation, disbursement, and liquidation. Quantitative findings indicate robust financial independence across all barangay income levels. However, qualitative insights reveal a complex reality: while independence fosters empowerment, policymaking, and social inclusion, it is simultaneously hampered by strict fidelity bonding, limited training, and rigorous liquidation requirements. To cope, officials employ best practices such as inter-council collaboration and professional engagement. The study concludes that while the legal framework successfully establishes financial autonomy, significant operational hurdles remain. These findings provide critical baseline data for government agencies to refine capacity-building programs, ensuring that SK financial independence translates into effective youth empowerment and accountable governance.